GAYA BELAJAR VISUAL, AUDITORI, DAN KINESTETIK TERHADAP PRESTASI AKADEMIK SISWA DI SMPN X AIRMADIDI - Alan Hubert Frederick Sanger; Fanny H. Rantung; Cimin B. Watumlawar; Juwinner Dedy Kasingku (Universitas Pahlawan Tuanku Tambusai, 2022)
This quantitative, descriptive, and correlational study aims to see whether there is a connection between students' academic achievement and the styles of learning, auditory, and kinesthetics. This questionnaire was filled out by 100 respondents, and convenience sampling was used to gather the information. According to the results of a study, kinesthetics learning is the most common type of learning for students, and their academic achievement comes into the good range. The three types of learning—visual, auditory, and kinesthetic—do not significantly differ from one another. It is recommended that teachers promote participation from students during the teaching and learning process by creating simulations, demonstrations, and exercises to help students comprehend the information being taught. Keywords: visual, auditory, kinesthetic, student academic achievement